(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Wound healing is a challenging clinical problem and there is a need of efficient wound management. Most of the time, wounds are accompanied by significant mortality as well as increased morbidity. Wound is a damage or disruption to the typical anatomical structure and function of skin which leads to the organ damage. The wound healing is divided into 4 phases according to their mechanism of action i.e Hemostasis, Inflammation, Proliferation and Remodeling. Several plants are used for the healing of wound. This review discusses the occurrence, classification of wound and treatment with the help of various plants and also discusses the mechanism of action of various phytoconstituents, which are responsible for wound healing.